PSYCHOLOGICAL NEGOTIATION OF HUSBAND AND WIFE IN THE DISTRIBUTION OF HOUSEHOLD ROLES: PSYCHOLOGICAL ANALYSIS OF ISLAMIC LAW - Aryani, Sophia; Hidayat, Taufik (International Journal of Multidisciplinary Reseach, 2026)
Social changes and the dynamics of modern life have influenced the pattern of marital relations in Indonesian Muslim households, especially in the distribution of domestic and public roles. This condition requires an adaptive mechanism so that marital relations remain harmonious and sustainable. This article aims to analyze the psychological negotiation of husband and wife in the distribution of household roles as well as its implications for family harmony and resilience from the perspective of Islamic legal psychology. This study uses a qualitative approach to the type of normative legal research based on literature studies, through the analysis of Islamic Family Law Literature, national scientific journals, and relevant academic works. The Data were analyzed descriptively-qualitatively to reveal the linkages between psychological factors, the distribution of household roles, and the principles of Islamic law. The results show that domestic conflicts in the context of contemporary Muslim families are not solely caused by violations of legal norms, but are more often triggered by emotional communication failures, role imbalances, and psychological pressures that are not negotiated fairly. Psychological negotiation acts as an internal mechanism that allows alignment between the normative demands of Islamic law and the psychological reality of the couple through the principles of deliberation, Justice and benefit. In the perspective of Islamic legal psychology, psychological negotiation is a substantive instrument to realize harmony, resilience, and sustainability of Muslim households in the midst of ongoing social changes.